1992
DOI: 10.1007/bf00300976
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prolonged neuropsychological testing on immunoregulatory cells and hormonal parameters in patients with systemic lupus erythematosus

Abstract: The influence of a 2-h neuropsychological stress test on plasma catecholamines, cortisol, and on the distribution of lymphocyte subpopulations was studied in 14 patients with systemic lupus erythematosus (SLE), 10 patients on prednisone treatment (without collagenosis), and 14 sex-and-age-matched healthy controls. Psychological stress induced comparably significant increases in plasma adrenaline and noradrenaline levels as compared with baseline values (P less than 0.05) in all three groups, whereas plasma cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 35 publications
0
20
0
3
Order By: Relevance
“…Fifteen studies included healthy participants without systemic inflammatory rheumatic disease as control and one study, patients with osteoarthritis [36,37]. In three studies a second control group was added, consisting of either patients with myofascial pain [32], patients with sarcoidosis [43], or participants taking corticosteroids [44]. Most studies have relatively small sample sizes (N = 10 to 20 per group), with even smaller sample sizes (N <10) in two studies [35,40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen studies included healthy participants without systemic inflammatory rheumatic disease as control and one study, patients with osteoarthritis [36,37]. In three studies a second control group was added, consisting of either patients with myofascial pain [32], patients with sarcoidosis [43], or participants taking corticosteroids [44]. Most studies have relatively small sample sizes (N = 10 to 20 per group), with even smaller sample sizes (N <10) in two studies [35,40].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies have relatively small sample sizes (N = 10 to 20 per group), with even smaller sample sizes (N <10) in two studies [35,40]. In addition, patient samples are probably heterogeneous because, for example, strict exclusion criteria regarding comorbidities are lacking in half of all studies [32,33,35,38,42-44,46]. With regard to diagnostic criteria, one study even included also patients with non-inflammatory arthritis [32].…”
Section: Resultsmentioning
confidence: 99%
“…É importante salientar que apenas três trabalhos demostraram alterações na resposta imune em pacientes com LES, após exposição a um estressor psicológico agudo, em condições laboratoriais (36)(37)(38) . O primeiro estudo com este objetivo foi realizado em 1992 por Hinrichsen et al, que verificaram a influência de um teste neuropsicológico de estresse no LES, através das alterações de catecolaminas plasmáticas, cortisol e na distribuição de subpopulações de linfócitos em 14 pacientes com LES comparados a 10 pacientes sem colagenose mas tratados com prednisona e 14 controles saudáveis.…”
Section: Inluência Do Estresse No Lesunclassified
“…Da mesma forma, as células CD19+ aumentaram significativamente em número com relação aos valores basais nos controles e nos tratados com prednisona, e permaneciam inalterados nos pacientes com LES. Os autores concluem que pacientes com lúpus demonstram redução da mobilização celular em razão do estresse psicológico, apesar de apresentarem alterações hormonais semelhantes aos outros dois grupos estudados (36) . Posteriormente, Pawlak et al também procuraram identificar alterações na freqüência cardíaca, pressão arterial, concentração de catecolaminas, subpopulações de linfócitos, atividade de células natural killer (NK) e expressão de ß-adrenoreceptores nos monócitos de sangue periférico após exposição a uma situação de estresse, no caso, falar em público.…”
Section: Inluência Do Estresse No Lesunclassified
“…For example, cognitive stressors elicited changes in leukocyte/lymphocyte counts, subsets of lymphocytes, and CRP levels in patients with RA (Geenen, 1998;Veldhuijzen van Zanten, 2005), and changes in leucocyte counts and cytoxic T cell numbers in patients with SLE (Hinrichsen, 1992). It has recently been demonstrated that thermal stress (Spa therapy) induces a reduction in the circulating levels of prostaglandin E2 (PGE2), leukotriene B4 (LTB4), IL-1 and TNF-, important mediators of inflammation and pain in patients with rheumatic diseases (Fioravanti, 2011).…”
mentioning
confidence: 99%